A facile synthesis of high entropy alloy nanoparticle–activated carbon nanocomposites for synergetic degradation of methylene blue. Issue 40 (14th July 2021) - Liu, Yuyu; Chen, Zheng; Yang, Xiaoqin; Zhang, Jinyong; Sun, Zhonggang; Chen, Yuzeng; Liu, Feng
Abstract : CoCrFeMnNi HEA NPs–AC were synthesized facilely with FCC solid solution phase and outstanding catalytic performance. The time required to reduce MB concentration can be as short as 12 min with the k obs of 0.191 min −1 for the 10 wt% catalyst. Abstract : Nanocomposites of CoCrFeMnNi high entropy alloy nanoparticle–activated carbon (HEA NPs–AC) were prepared by a facile and controllable impregnation–adsorption method. The HEA NPs–AC showed excellent catalytic performance in the degradation of methylene blue (MB) without any peroxide addition. Besides, their reaction rate is also competitive among single-element and other catalysts. The outstanding efficiency is attributed to the coupling effects of the solid-solution structure of HEA NPs, and the large specific surface area and substantial reaction channels of AC. Moreover, the HEA NPs embedded in distinctive porous architectures accelerate the electron transfer and the mass transport as nanoscale galvanic cells in active bond breaking of MB. The nanocomposites of HEA NPs–AC are distinguished by containing non-noble metals and having high catalytic performance due to the synergetic degradation, providing a better alternative for efficient metal catalysis.